Model Integrasi Sains dan Agama dalam Pendidikan Nasional - Muhammad Miftah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Religious education in primary schools has often been used merely as a complement to the learning process. Government attention and commitment to developing religious education remain limited to fulfilling the obligations mandated by existing legislation. The thematic and integrative approach in Curriculum 2013 provides new hope for religious education, enabling it to be integrated with other subjects in the learning process. The implementation of Curriculum 2013 was driven by the emergence of deviant behavior among students, ranging from moral decline to the erosion of students’ character. The new breakthroughs introduced in Curriculum 2013 are expected to address various social issues in education. This paper seeks to reveal the integration model of religion and science in the new curriculum, particularly through the unification of subjects. This integration is carried out by incorporating basic competencies into themes related to nature and the environment in daily life. The integration of subject materials into several themes is expected to help students develop a holistic understanding of the material, rather than a partial one.